2012
DOI: 10.1007/s10658-012-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling in the roots of coffee plants exposed to the coffee root-knot nematode, Meloidogyne exigua

Abstract: To understand the effect of nematode Meloidogyne exigua infestation on coffee plants, resistant and susceptible coffee seedlings were inoculated with second-stage juveniles of M. exigua, and root metabolites were studied for four time intervals at 0, 24, 48 and 96 h. During this important period for parasite establishment, the concentrations of phenols, carbohydrates, amino acids and alkaloids in the roots were measured, and hydrogen nuclear magnetic resonance spectra of the root extracts were used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…21,22 Other important negative loadings on PC1 are in the region of d 6.66-7.30, characteristic of phenolic compounds, which are a widespread group of defensive substances with an important role in phytoparasitic defense. 2,8 A signal at d 7.92 was observed and could be assigned to xanthine. 23 Besides being related to the maturation process of this plant, these kinds of compounds are powerful natural allelochemicals that can repel and inhibit the phytoparasite development.…”
Section: Metabolic Profile Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Other important negative loadings on PC1 are in the region of d 6.66-7.30, characteristic of phenolic compounds, which are a widespread group of defensive substances with an important role in phytoparasitic defense. 2,8 A signal at d 7.92 was observed and could be assigned to xanthine. 23 Besides being related to the maturation process of this plant, these kinds of compounds are powerful natural allelochemicals that can repel and inhibit the phytoparasite development.…”
Section: Metabolic Profile Screeningmentioning
confidence: 99%
“…Since current nematode control methods present many disadvantages, such as difficulty of implementation in some areas and high cost, there is an increasing demand for new safe methods that prevent human and environmental contamination with toxic substances. 1,2 Several nematicidal substances have been isolated from plants and can be considered possible alternatives. 1 Secondary metabolites reported as potential phytonematode controlling agents may present unique and complex chemical structures belonging to different classes of natural products, such as alkaloids, terpenes, tannins, flavonoids glycosides, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Many analytical techniques were employed for the characterization and identification of trigonelline 3,9 . Machado et al 10 observed by NMR spectroscopy a content of 1.20 mg·g -1 of trigonelline in Coffea Arabica roots. NMR in particular, is a non-targeted analytical technique where there is no need for previous separations, derivates and even purification with processes being quick and efficient and capable to simultaneously detect a large amount of metabolites in only one analysis 11 .…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies already indicate that a complex network of secondary metabolites is influenced by biotic stress challenges. Next to phenylpropanoids, including flavonoids [34,50,51,71], alkaloids [72,73], terpenoids [33], and fatty acids [74] are also known to be up-regulated [25]. In addition, lipids act under pathogen or herbivore attack as mechanical barriers.…”
Section: From Biotic Stress Metabolomics To Metabolic Responsementioning
confidence: 99%